Quality analysis of marine zooplankton oils and identification of target molecules - Benini, Lorenzo (Alma Mater Studiorum - Università di Bologna, 2023)
With the increase in population, the demand for fish, for both human consumption and fish feed in aquaculture, has become highly competitive. This growth has led to an increased demand for fish oil. In order to meet the growing nutritional needs of fish, feed must provide essential elements such as polyunsaturated fatty acids, astaxanthin, proteins, and amino acids. Furthermore, there is a growing interest in finding new alternatives for fish feed production and, especially, in fish oil and dietary supplements for human consumption. The use of secondary raw materials and byproducts from fish processing has become a solution to alleviate the pressure on wild resources and reduce waste. These byproducts are often rich in valuable ingredients, such as astaxanthin, chitin, collagen, and marine oils. Additionally, sustainable, and eco-friendly methods are being developed for the recovery of oils and other valuable components, avoiding the use of harsh chemicals. The aim of this study was to extract oil from a zooplankton-rich side-stream obtained from pelagic processing, focusing on the visceral content of atlantic mackerel (Scomber scombrus), using two different extraction methods. The study also involved comparing the yield and composition of each extraction method and comparing it to five commercially available oils derived from different raw material origins. The chemical properties and compositions of the oils were also analyzed.